SOCIAL SUPPORT, SOCIAL SKILLS DEVELOPMENT, AND EXTERNALIZED BEHAVIOR PROBLEMS IN ADOLESCENTS WITH MILD INTELLECTUAL DISABILITY - Bojana Arsić (Istraživanja u Pedagogiji, 2025)
The aim of the research was to examine the perception of social support among adolescents with mild intellectual disability (MID) and its relationship with externalized behavior problems and social skills. The research was conducted using a quantitative method, applying descriptive and inferential statistics through the SPSS software for data analysis. The sample included 33 students with MID, aged between 15 and 20 years, attending a school for the education and upbringing of students with intellectual developmental difficulties. Instruments were used to assess social support, externalized behavior problems, and social skills, and these were completed by both teachers and the students themselves. The respondents perceived the highest level of social support from teachers and the lowest from classmates, with this difference being statistically significant. Male participants perceived a higher level of parental support than female participants, while those from intact families reported significantly higher support from classmates. Correlation analyses showed a high level of interconnection between different sources of social support. No correlation was found between social support and externalized behavior problems, while externalized behavior problems were negatively correlated with socialization. The results highlight the significant role of teachers and parents in providing support to adolescents with MID, while peer support remains relatively low. It was also found that gender and family structure influence the perception of social support. On average, the participants exhibited a low level of externalized behavior problems and well-developed social skills, which may be attributed to environmental support and rehabilitation programs. Future research should focus on larger samples and include individuals with more severe forms of intellectual disabilities.